Anchorless implant for the treatment of advanced anterior and apical vaginal prolapse – Medium term follow up. (March 2020) - Levy, Gil; Padoa, Anna; Marcus, Naama; Beck, Anat; Fekete, Zoltan; Cervigni, Mauro
Abstract: Objective: to evaluate the mid-term safety and efficacy of a surgical technique using an anchorless implant. Study design: This is a prospective study. Women with symptomatic POP were recruited. The technique involved placement of an open trapezoid-shaped frame which retains a polypropylene mesh stretched within its parameter. No fixation techniques used. Demographic data and pre-operative quality of life (QoL) questionnaires were collected. Peri-operative data were documented. Patients were followed at 2, 6, 12, 24 and 36 months. Follow-up included repeated QoL questionnaires, Pelvic Organ Prolapse- Quantification (POP-Q) measurements and assessment for possible complications. Results: Seventy women were recruited. Mean age was 63.1 years, mean parity was 4.6 deliveries. Mean pre-operative POP-Q were Ba = 3.1 (-1 to 6) cm and C = 0.4 (-8 to 6) cm. No intra-operative complications were observed. Surgical time averaged 24.7 min. Estimated blood loss averaged 155 cc. Mean follow up at last visit was 27.7 months. Two patients (2.8 %) underwent partial frame resection and two patients (2.8 %) underwent a TVT-O for de-novo stress urinary incontinence (SUI). At follow-up, the mean POP-Q were Ba= -2.8 (-3 to -1) cm and C = -6.8 (-10 to 1) cm. Two patients (2.8 %) had recurrent prolapse. One was symptomatic and received treatment. No mesh erosion or chronic pelvic pain were documented. Pelvic Function Distress Inventory (PFDI20) scores showed significant improvement. Thirty-eight (54 %) patients completed the Pelvic organ prolapse/Urinary Incontinence Sexual Questionnaire (PISQ12) showing no chronic dyspareunia. Conclusion: The Self Retaining Support (SRS) implant provides 97 % subjective and 94.3 % objective cure. Two patients (2.8 %) had the implant's frame removed surgically. The SRS is a safe and effective treatment for pelvic organ prolapse.